GAYA KEPEMIMPINAN KEPALA DESA DALAM MEMBANGUN PARTISIPASI MASYARAKAT DI BIDANG PEMBANGUNAN INFRASTRUKTUR DI KABUPATEN PESAWARAN - Tia Marlinda Sari; Putri Rahmaini; Goestyari Kurnia Amantha (Jurnal Progress Administrasi Publik (JPAP), 2023)
Leadership style is a leader's behavior that is used by someone when they want to influence the people they lead. The potential that exists in District, Pesawaran Regency is very large, but the utilization of all existing potentials is still not optimal in its empowerment. The village head's leadership style determines how to optimize the empowerment of the potentials that exist in the village. This is what makes researchers interested in choosing Sukaraja Village as a research location. The purpose of this study was to find out the leadership style of the village head in building community participation in infrastructure development in District, Pesawaran Regency in 2020. The research method used by researchers was qualitative research. The techniques used in collecting data by means of observation, interviews and documentation. The data analysis technique used is interactive model analysis which includes data reduction, data presentation and verification. He results of the research and discussion of the village head's leadership style in building community participation in District, Pesawaran Regency in 2020 can be concluded as follows: (1) The village head has a Laissez Faire leadership style. (2) The village head uses the concept of interpersonal roles and informational to build community participation. (3) The output of the village head's leadership style in building community participation in his village, is that the potential of natural resources is managed and the potential for human resources is quite good but not optimal.   Keywords  : Leadership Style; Society Participation.